PROPERTIES OF BIPOLAR FUZZY HYPERGRAPHS - Akram, M.; Dudek, W.A.; Sarwar, S. (Italian Journal of Pure and Applied Mathematics, 2013)
In this article, we apply the concept of bipolar fuzzy sets to hypergraphs and investigate some properties of bipolar fuzzy hypergraphs. We introduce the notion of A− tempered bipolar fuzzy hypergraphs and present some of their properties. We also present application examples of bipolar fuzzy hypergraphs.